KONTEKSTUALISASI KEADILAN DALAM HUKUM QISASH : (PERSPEKTIF QS. AL-MAIDAH AYAT 45) - Muhammad, Fauzyl; Jani Arni (Department of Ilmu al-Qur'an dan Tafsir, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2024)
The law of qisas is one part of Islamic criminal law, also known as fiqh al-jinayah. Islamic criminal law or fiqh al-jinayah encompasses all legal provisions regarding criminal acts committed by humans, especially accountable individuals, and as jurisprudence, it is the result of understanding the detailed legal evidence in the Quran and Hadith. Qisas is one of God's rules that must be implemented. Despite the disagreements among legal experts regarding the procedures for implementing qisas, there are principles of justice that should be considered and cannot be found in the implementation of other laws. This is part of God's Justice, which always seeks the welfare of humanity. The qisas law we examined uses the perspective of the Quran, specifically Surah al-Maidah verse 45, focusing on the contextualization of justice in qisas law.